2018
DOI: 10.12816/0044531
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Prostate Cancer, Screening and Methods of Managements in a Hospital in Riyadh, Saudi Arabia

Abstract: Background: screening for prostate cancer (PCa) is surrounded by controversies regarding the benefits, risks and uncertainties of undergoing the screening. Current practices of prostate cancer involve measuring the level of PSA and digital rectal examination. This study aimed to measure the knowledge and awareness of undergoing a prostate cancer screening and the available treatment options amongst the participants. Method: a questionnaire-based quantitative cross-sectional study which focuses on determining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…As noted in our study and previous ones, sociodemographics and educational levels have been found to positively impact awareness and overall knowledge of PCa. [ 15 22 28 ] Surprisingly, only 15.9% of our participants who have a positive family history of PCa had good knowledge. This lack of knowledge of PCa necessitates putting efforts into educating men for decision-making regarding PCa screening activities.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As noted in our study and previous ones, sociodemographics and educational levels have been found to positively impact awareness and overall knowledge of PCa. [ 15 22 28 ] Surprisingly, only 15.9% of our participants who have a positive family history of PCa had good knowledge. This lack of knowledge of PCa necessitates putting efforts into educating men for decision-making regarding PCa screening activities.…”
Section: Discussionmentioning
confidence: 78%
“…[ 21 ] The most recent regional study was done in Riyadh and showed that 82.3% of participants heard about PCa and 37.8% did not know the symptoms of PCa. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Sample of 337 expatriate men performed this research and an appropriate sample was selected with a drop-out rate of 27 percent. Paiva, Motta, & Griep, 2010;Almuhanna et al, 2018). The variations reviewed can be explained by differences in the population groups analyzed, as a study done by the Almuhanna et al (2018), found that higher levels of academic achievement are markedly associated with the level of Knowledge (P-value < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Paiva, Motta, & Griep, 2010;Almuhanna et al, 2018). The variations reviewed can be explained by differences in the population groups analyzed, as a study done by the Almuhanna et al (2018), found that higher levels of academic achievement are markedly associated with the level of Knowledge (P-value < 0.001). The major limitation of the current study was a sample which may not be considered entirely representative of the population researched.…”
Section: Resultsmentioning
confidence: 99%
“…An early detection through screening and timely treatment provides the greatest chance for increasing the 5-year survival rate. If the cancer is diagnosed during the early stages, the PCa prognosis is more optimistic (1,2,3) .…”
Section: Introductionmentioning
confidence: 99%